Reduced efficiency roll-off in light-emitting diodes enabled by quantum dot-conducting polymer nanohybrids - Bae, Wan Ki; Lim, Jaehoon; Zorn, Matthias; Kwak, Jeonghun; Park, Young-Shin; Lee, Donggu; Lee, Seonghoon; Char, Kookheon; Zentel, Rudolf; Lee, Changhee (ROYAL SOC CHEMISTRY, 2014)
We demonstrate QLEDs implementing wider active layers (50 nm) based on QD-conducting polymer nanohybrids, which exhibit a stable operational device performance across a wide range of current densities and brightness. A comparative study reveals that the significant suppression of efficiency roll-off in the high current density regime is primarily attributed to a sufficient charge carrier distribution over the wider active layer and improved charge carrier balance within QDs enabled by the hybridization of QDs with conducting polymers. Utilization of this finding in future studies should greatly facilitate the development of high performance, stable QLEDs at high current density or luminance regime toward displays or solid-state lighting applications.
Keywords: NANOCRYSTAL SOLIDS; CHARGE INJECTION; DEVICES; LAYERS